Makanan Pantangan pada Ibu Hamil Kekurangan Energi Kronik (KEK) - Farida Sisni Riyanti; Andi Nilawati Usman; Werna Nontji; Isharyah Sunarno; Stang Stang; Yuliana Syam (Journal of Telenursing (JOTING), 2023)
This study aims to determine dietary restrictions in pregnant women on the incidence of chronic energy deficiency (KEK) at the Sumbersari Health Center. The qualitative method with an exploratory phenomenology approach was analyzed using the Collaizi method. The results showed five themes related to food taboos for pregnant women: knowledge of pregnant women, types of food taboos for pregnant women, cultural background, family and social environment perceptions and efforts of pregnant women to prevent SEZs from occurring. In conclusion, food restrictions in pregnant women are one of the triggering factors for KEK, which are influenced by the culture that is owned by the family and passed down from their ancestors. Keywords: Mother, Pregnancy, Chronic Energy Deficiency, Food Restrictions